2015
DOI: 10.1080/15391523.2015.999640
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Quality of Technology Implementation in STEM Classrooms: Demonstration of an Evaluative Framework

Abstract: Technology applications aligned with science, technology, engineering, and math (STEM) workplace practices can engage students in real-world pursuits but also present dramatic challenges for classroom implementation. We examined the impact of teacher professional development focused on incorporating these workplace technologies in the classroom. Because existing measures primarily use only presence or type of technology as proxies for implementation quality, we developed an expanded framework that incorporated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
0
9
0
2
Order By: Relevance
“…The idea of employing TPACK for the study of STEM education has been proposed and tested in limited contexts. Parker et al investigated science teachers' quality of technology use with reference to the Next Generation Science Standards and found that high-quality use was limited [19]. Yildrim and Sidekli employed the TPACK framework in preservice teacher development by integrating technology in teaching mathematics in the context of STEM education [33].…”
Section: Learning By Designing To Develop Teachers' Tpackmentioning
confidence: 99%
See 3 more Smart Citations
“…The idea of employing TPACK for the study of STEM education has been proposed and tested in limited contexts. Parker et al investigated science teachers' quality of technology use with reference to the Next Generation Science Standards and found that high-quality use was limited [19]. Yildrim and Sidekli employed the TPACK framework in preservice teacher development by integrating technology in teaching mathematics in the context of STEM education [33].…”
Section: Learning By Designing To Develop Teachers' Tpackmentioning
confidence: 99%
“…Nonetheless, when STEM education is anchored with engineering design challenges, students will encounter authentic engineering problems, which will require them to use ICT as a productive, collaborative, and cognitive tool to help them gather, synthesize, model, and construct the knowledge needed [30]. This could address the problems reported earlier about teachers not using ICT as a cognitive tool to engender 21st century student-centered learning [19,27,28]. In addition, the latest advanced technologies, such as 3D printing, micro-computers, and block-based coding environments afford teachers and students ample opportunities to compute and make functional prototypes [40].…”
Section: Interdisciplinary Stem and Tpackmentioning
confidence: 99%
See 2 more Smart Citations
“…The Protocol builds on a published theoretical framework that consists of four dimensions: technology type, science and engineering practices (SEPs), student-centered teaching, and relevance to students' lives (Parker, Stylinski, Bonney, Schillaci & McAuliffe 2015). These dimensions are critical to highquality technology integration, and their inclusion in our observation protocol supports the instrument's content validity.…”
Section: Theoretical Foundation Of the Protocolmentioning
confidence: 99%